The Effect of the Medium and the Variety on the Yield of Shallots (Allium ascalonicum L.) Grown in a Polybag - Marta, Nini; Kuswandi, Kuswandi; Andini, Mega; Sunyoto, Sunyoto; Irawati, Yulia; Nofiarli, Nofiarli; Nasution, Fitriana (Journal of Tropical Horticulture, 2020)
Shallot is an important spice and seasoning in Indonesia. It is consumed almost daily in many dishes. The objective of this experiment was to study the effect of the medium and the variety on the yield of shallots grown in a polybag. The experiments were arranged in a two-factorial randomized complete block design with three replications. The factors were medium (1 soil: 1 paddy husk ash and 1 soil: 1 compost) and variety (Agrihorti 1 and Mentes). Data were statistically analyzed by Analysis of Variance (ANOVA), and the means were compared using Honestly Significant Difference (HSD) at P < 0.05. There was no interaction between medium and variety. Overall, all treatments did not significantly affect yield. Varieties were significant differences on bulb diameter; however, they were not significant differences on bulb height, fresh bulb weight per polybag, and bulb number per polybag. Those media are considered as precise media due to they contain organic materials.